MAKING KIN: POSTHUMAN IDENTITY IN ANNE HAVERTY’S "ONE DAY AS A TIGER" AND KAREN JOY FOWLER’S "WE ARE ALL COMPLETELY BESIDES OURSELVES" - PARASCHIV, Paul Mihai (Studia Universitatis Babeș-Bolyai Philologia, 2022)
Making Kin: Posthuman Identity in Anne Haverty’s One Day as A Tiger and Karen Joy Fowler’s We Are All Completely Besides Ourselves. Through discussions on anthropomorphism, animal research and posthuman sensibilities, this paper intends to analyse how identity is shaped within the human characters so as to account for practices of kinship and to promote a posthuman model that emancipates from the anthropocentric milieu. In the encounter with narratives that have at their core human-animal interactions, we are generally placed in the position to inquire about the development of identity. Paying closer attention to the emergence of new sensibilities within the human subject in relation to the otherness of the animal, we discover that these narratives can have a tendency to instantiate posthuman becomings and introduce characters that transgress the discriminating “line” that is discussed by Margo DeMello. The “line” itself, although operating through a process of othering, is essentially prejudicial as it aids the creation of species hierarchies. Such is the case with Anne Haverty’s protagonist Marty in One Day as a Tiger and Karen Joy Fowler’s character Rosemary in We Are All Completely Besides Ourselves. The human subjects in these narratives enter relations of kinship with their animals and in doing so, they manage to build patterns for kin-making as a key to eradicate speciesism. Therefore, looking at the differing reactions to animal alterity in the eyes of the human, I hope to capture the plurality of these encounters. Article history: Received 27 February 2022; Revised 16 May 2022; Accepted 26 May 2022; Available online 30 June 2022; Available print 30 June 2022. REZUMAT. Înrudirea: Identitatea postumană în One Day as a Tiger de Anne Haverty și în We Are All Completely Besides Ourselves de Karen Joy Fowler. Prin intermediul discuțiilor despre antropomorfism, cercetarea asupra animalelor și sensibilitățile postumane, această lucrare își propune să analizeze felul în care se modelează identitatea personajelor umane, astfel încât să ofere o explicație pentru practicile de înrudire și să promoveze un model postuman care să se emancipeze de mediul antropocentric. Atunci când ne întâlnim cu narațiuni care au în centrul lor interacțiunile om-animal, suntem în general puși în situația de a investiga dezvoltarea identității. Acordând o atenție sporită apariției unor noi sensibilități pentru subiectul uman în raport cu alteritatea animalului, descoperim că aceste narațiuni pot avea tendința de a instanția deveniri postumane și de a introduce personaje care transgresează “linia” discriminatorie pe care o prefigurează Margo DeMello. "Linia" în sine, deși operează printr-un proces de diferențiere, este în esență prejudiciabilă, deoarece ajută la crearea de ierarhii între specii. Acesta este cazul protagonistului Marty al lui Anne Haverty din One Day as a Tiger și al personajului Rosemary al lui Karen Joy Fowler din We Are All Completely Besides Ourselves. Subiecții umani din aceste narațiuni intră în relații de rudenie cu animalele lor și, în acest fel, reușesc să construiască modele de înrudire ca o cale de eradicare a speciismului. Prin urmare, analizând reacțiile diferite la alteritatea animalelor prin ochii oamenilor, sper să surprind pluralitatea acestor întâlniri. Cuvinte-cheie: postumanism, speciism, înrudire, identitate, devenire, antropomorfism